2010
DOI: 10.1007/s12671-010-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Cigarette Cravings: Comparison of Suppression Versus Mindfulness-Based Strategies

Abstract: Mindfulness-and acceptance-based therapies have been explored within the context of addiction treatment, with some preliminary success. The current empirical study investigated the effectiveness of a brief suppression versus mindfulness-based strategy for coping with cigarette cravings. Participants (N =61; M age= 40.34 years, SD=12.42) were randomly assigned to using one of the two coping strategies to help them manage cravings during an experimental cue exposure to cigarettes. Participants completed self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 73 publications
(80 reference statements)
2
87
0
3
Order By: Relevance
“…Mindfulness practice may disrupt the relapse cycle by weakening the associative link between craving and use Elwafi et al, 2013;Ostafin, Bauer, & Myxter, 2012;Rogojanski, Vettese, & Antony, 2011).…”
Section: Mindfulness-based Treatment For Substance Use Disordersmentioning
confidence: 99%
“…Mindfulness practice may disrupt the relapse cycle by weakening the associative link between craving and use Elwafi et al, 2013;Ostafin, Bauer, & Myxter, 2012;Rogojanski, Vettese, & Antony, 2011).…”
Section: Mindfulness-based Treatment For Substance Use Disordersmentioning
confidence: 99%
“…Four of the studies delivered the mindfulness intervention in an outpatient setting (Davis, Mills, et al, 2013;Davis, Goldberg, et al, 2014a;Davis, Manley, et al, 2014b;Tang, Tang, and Posner, 2013). In four of the studies, it was unclear where the intervention was delivered (Bowen and Marlatt, 2009;Brewer et al, 2011;Rogojanski, Vettese, and Antony, 2011a;Singh et al, 2014).…”
Section: Settingmentioning
confidence: 99%
“…One of the studies utilized integrative body-mind training (Tang, Tang, and Posner, 2013). Three of the studies described their interventions as mindfulness training, mindfulness meditation, and mindfulness-based smoking cessation program (Brewer et al, 2011;Rogojanski, Vettese, and Antony, 2011a;Singh et al, 2014).…”
Section: Interventionsmentioning
confidence: 99%
“…However, these studies are limited in that they did not differentiate between suppressing thoughts of smoking specifically or other thoughts (Haaga & Allison, 1994;Nosen & Woody, 2009;Rogojanski et al, 2011aRogojanski et al, , 2011b. In addition, Litven, Kovacs, Hayes, and Brandon (2012) observed that both suppression and acceptance strategies were associated with less craving and affect compared with the controls.…”
Section: Introductionmentioning
confidence: 99%
“…postulated that suppression may exacerbate cigarette cravings, increasing desire to smoke and smoking behavior. Some studies have not found an association between thought suppression and increased smoking (Haaga & Allison, 1994;Nosen & Woody, 2009;Rogojanski, Vettese, & Antony, 2011a, 2011b.…”
Section: Introductionmentioning
confidence: 99%